Perpetrators' Perceptions of Infidelity Cases Regarding Infidelity Through Social Media - Hendra Yani (Penerbit Hellow Pustaka, 2025)
This study aims to understand the perception of individuals involved in infidelity cases regarding their actions through social media, as well as to identify the driving factors behind such behavior. The increasing number of divorces caused by infidelity in the digital era serves as the primary background of this research, particularly in Karamaian Village, Masalembu District, Sumenep Regency. This research employs a qualitative approach with a phenomenological method to explore the subjective experiences of those involved in infidelity. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the participants' perceptions of infidelity vary, ranging from justification due to discomfort in marriage to emotional attraction developed through social media interactions. The main contributing factors include loveless marriages, economic pressure, lack of attention from spouses, and opportunities created by social media platforms. Data show that 15% of total divorce cases in Karamaian Village are caused by infidelity via social media. This study highlights the importance of digital literacy, healthy interpersonal communication within the household, and the reinforcement of religious values to prevent infidelity in the technological era.